Measuring Kinetic Dissociation/Association Constants Between Lactococcus lactis Bacteria and Mucins Using Living Cell Probes - Le, Doan Thanh Lam (The Biophysical Society, 2011)
In this work we focused on quantifying adhesion between Lactococcus lactis, the model for lactic acid bacteria (LAB) and mucins. Interactions between two strains of L. lactis (IBB477 and MG1820 as control) and pig gastric mucin–based coating were measured and compared with the use of atomic force microscopy. Analysis of retraction force-distance curves shed light on the differential contributions of nonspecific and specific forces. An increased proportion of specific adhesive events was obtained for IBB477 (20% vs. 5% for the control). Blocking assays with free pig gastric mucin and its O-glycan moiety showed that oligosaccharides play a major (but not exclusive) role in L. lactis-mucins interactions. Specific interactions were analyzed in terms of kinetic constants. An increase in the loading rate of atomic force microscope tip led to a higher force between interacting biological entities, which was directly linked to the kinetic dissociation constant (K(off)). Enhancing the contact time between the tip and the sample allowed an increase in the interaction probability, which can be related to the kinetic association constant (K(on)). Variations in the loading rate and contact time enabled us to determine K(on) (3.3 × 10(2) M(−1)·s(−1)) and K(off) (0.46 s(−1)), and the latter was consistent with values given in the literature for sugar-protein interactions.